2017
DOI: 10.3892/ol.2017.6454
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 influences the characteristics of stem cells in cervical carcinoma

Abstract: The purpose of the study was to investigate the role of the signal transducer and activator of transcription 3 (STAT3), signal transduction protein in regulating the biological characteristics of stem cells in cervical carcinoma. Overexpressed plasmid of STAT3 was constructed and used to transfect SiHa into cervical carcinoma cells. STAT3-targeted specific siRNA was designed and produced. The effects of STAT3 upregulation (or inhibition) on the expression of NANOG, OCT4 and SOX2 markers of stem cells were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 22 publications
(20 reference statements)
0
17
0
Order By: Relevance
“…Recent results reported by Wang H et al [ 40 ] suggested that SOX2 and NANOG are the key downstream proteins of STAT3 signaling pathways in cancer. SOX2 and NANOG are transcription factors and biomarkers for cancer stem cells (CSCs) [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent results reported by Wang H et al [ 40 ] suggested that SOX2 and NANOG are the key downstream proteins of STAT3 signaling pathways in cancer. SOX2 and NANOG are transcription factors and biomarkers for cancer stem cells (CSCs) [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in line with finding that DE-EDCP treatment markedly reduced expression of STAT3 at protein and mRNA level in vitro , immunohistochemistry analysis showed a similar trend for decreased percentage of Y705 phospho-STAT3-positive cells within breast cancer tissue of DE-EDCP treated mice compared to control group, although this difference did not reach statistical significance (Figure 7C and 7D ). A previous report demonstrated that knockdown of STAT3 protein in cervical carcinoma cell line by siRNA reduced mRNA and protein expressions of NANOG and SOX2 [ 40 ]. Accordingly, data obtained from our study indicated that reduction in STAT3 expression after DE-EDCP treatment resulted in significantly lower expression of NANOG and SOX2 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that STAT3 is an important regulator for self-renewal and survival of CSCs in various tumors [40]. In cervical carcinoma, STAT3 upregulates the stem-like characteristics of cervical cancer cells by increasing the expression of the stemness supporting markers such as Sox2, Oct4, and Nanog [29,30]. Therefore, targeting STAT3 signaling may be a promising approach to combat the survival of cervical CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Pterostilbene treatment more noticeably decreased the expression levels of stemness markers compared with resveratrol treatment. The STAT3 pathway is involved in the maintenance of cervical CSCs by regulating the expression of stem cell-related transcription factors [29,30]. To further understand the molecular mechanism underlying the anticancer effects of resveratrol and pterostilbene against cervical CSCs, we investigated whether the two compounds affect STAT3 signaling.…”
Section: Effect Of Pterostilbene On the Expression Of Stemness Markermentioning
confidence: 99%
“…Aberrant expression and persistent activation of STAT3 is implicated in cell proliferation, differentiation, apoptosis and immune escape, inducing and maintaining a pro-carcinogenic inflammatory microenvironment [ 7 ]. Continuously activated STAT3 has been found in many human tumors, such as lung cancer [ 8 ], gastric carcinoma [ 9 ], cervical carcinoma [ 10 ], and meningiomas [ 11 ]. Moreover, mounting evidence have demonstrated STAT3-targeted therapy could effectively inhibit tumor development in various human cancers [ 12 ].…”
Section: Introductionmentioning
confidence: 99%